ANALISA KADAR ALKOHOL PADA SUSU FERMENTASI BERDASARKAN LAMA PENYIMPANAN LEMARI ES - Mardiyah, Siti (Universitas Muhammadiyah Surabaya)
ANALISA KADAR ALKOHOL PADA SUSU FERMENTASI BERDASARKAN LAMA PENYIMPANAN LEMARI ESSiti Mardiyah, S.Si, M.Kes.Sitimardiyahfix2@gmail.com Prodi D3 Analis Kesehatan UM SurabayaÂ AbstractFermented milk is one of dairy products, obtained by fermentation of milk by certain microbes to produce lactic acid. In general, fermented milk stored at a temperature of 50C cooler cupboard to inhibit acid formation by bacteria is still alive, so as to avoid excessive formation of a sour taste. During storage of fermented milk pH decreased continuously. At a temperature of 100C, the damage began to emerge after 3-4 days of storage, which is a sour, watery, and the accompanying changes in the original tender texture and cause contamination between certain bacteria that cause alcohol. Based on the above formulation of the problem can be taken